2018
DOI: 10.1021/acs.oprd.8b00282
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of Thermochemical Depolymerization of Lignin Model Compounds in the Presence of Novel Liquidlike Nanoparticle Organic Hybrid Solvents for Efficient Biomass Valorization

Abstract: This study reports the thermochemical transformation of lignin model compounds using nanoparticle organic hybrid materials (NOHMs). NOHMs have recently been developed as an emerging class of self-suspended nanoparticle solvent systems created by ionically or covalently grafting organic oligomers or polymers (canopy) onto surface-modified inorganic nanoparticles (core). Because NOHMs exhibit negligible vapor pressure with the ability to tailor physicochemical properties, they could be a promising catalytic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…As an emerging class of “green” solvent, nanoparticle organic hybrid materials (NOHMs) have been proposed. NOHMs are self-suspended nanoparticle-based functional materials that consist of a surface-functionalized inorganic nanocore, with oligomeric or polymeric chains that are referred to as a “canopy”. The canopy can be bonded to the corona-like nanocore either covalently or ionically .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an emerging class of “green” solvent, nanoparticle organic hybrid materials (NOHMs) have been proposed. NOHMs are self-suspended nanoparticle-based functional materials that consist of a surface-functionalized inorganic nanocore, with oligomeric or polymeric chains that are referred to as a “canopy”. The canopy can be bonded to the corona-like nanocore either covalently or ionically .…”
Section: Introductionmentioning
confidence: 99%
“…This results in versatile physicochemical characteristics that range from those of glassy solids to solvent-free nanoparticle fluids. ,, To date, a variety of core materials including metal oxides, ,,, metals, , carbon nanotubes, fullerenes, and silsesquioxanes have been designed and synthesized using structural variations of organic canopy materials. Because NOHMs exhibit negligible vapor pressure and enhanced thermal stability, they can be utilized as green solvents in diverse areas of application by adding task-specific functional groups along the canopy materials and/or to the nanocore. The applications involving NOHMs that have been investigated thus far include thermal management fluids, lubricants, magnetic fluids, , nanocomposites, electrolytes, water treatment and biomass pretreatment chemicals, and CO 2 capture solvents. ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…With the development of scientific understanding of lignin and the application of new catalysts, many new strategies of lignin degradation have been proposed. These current technologies can be generalized into acid/base catalyzed depolymerization ( Dabral et al., 2018 ; Lindsay et al., 2019 ; Liu et al., 2019a ; Nagel and Zhang, 2019 ; Zhu et al., 2018 )/hydrolysis ( Deuss et al., 2015 ; Nichols et al., 2010 ; Sedai et al., 2011 ; Sergeev et al., 2012 ), pyrolysis ( Boerjan et al., 2003 ; Das et al., 2018 ; Kim et al., 2019 ; Li et al., 2018 ; Luo et al., 2019 ; Moon et al., 2018 ; Rinesch and Bolm, 2018 ; Zhang et al., 2018 )/metal-catalyzed bond cleavage ( Díaz-Urrutia et al., 2016 ; Gazi et al., 2015 ; Hanson et al., 2012 ; Jiang et al., 2016 ; Sedai et al., 2013 )/photochemical lignin degradation ( Ahmad et al., 2010 ; Bosque et al., 2017 ; Cao et al., 2018 ; Chen et al., 2017 , 2020 ; Enright et al., 2019 ; Hao et al., 2018 ; Karkas et al., 2016 ; Li et al., 2019a , 2019b , 2020 ; Liu et al., 2019b ; Luo et al., 2017a , 2017b ; Nguyen et al., 2014 , 2019 ; Srisasiwimon et al., 2018 ; Wu et al., 2018 ; Zhang, 2018 ; Zhou et al., 2018 ), and even biodegradation ( Dabral et al., 2017 ; Ragauskas et al., 2014 ). Lignin degradation under acidic conditions is one of the most classical technologies.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Significant works have proposed and deployed methods to mitigate anthropogenic CO 2 emissions, particularly those linked to the combustion of fossil fuels. 5,6 Among the promising strategies being considered for the mitigation of anthropogenic CO 2 are carbon capture and storage (CCS) technologies, which capture CO 2 from the flue gas streams of large point source fossil fuels, transport it to a storage site, and keep it from entering the atmosphere. 7,8 Carbon mineralization has been widely accepted as an attractive option for CO 2 storage since it serves double duty, both as CO 2 storage and utilization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Without proper worldwide efforts it is expected that global average temperatures will further dramatically increase as a consequence . As part of ongoing global efforts, in 2018 the Intergovernmental Panel on Climate Change (IPCC) suggested that the rise in global temperature has to be limited to between 1.5 and 2 °C, compared to that of the preindustrial revolution. , Significant works have proposed and deployed methods to mitigate anthropogenic CO 2 emissions, particularly those linked to the combustion of fossil fuels. , …”
Section: Introductionmentioning
confidence: 99%